Concise Access to the Skeleton of Protoilludane Sesquiterpenes through a Photochemical Reaction Cascade: Total Synthesis of Atlanticone C. (3rd September 2019) - Zech, Andreas; Jandl, Christian; Bach, Thorsten
Abstract: In a single photochemical operation ( λ ≥350 nm) an easily accessible indanone derivative was converted into a structurally complex precursor of the protoilludane sesquiterpenes. The product (60 % yield) contains all 15 carbon atoms of the skeleton in the required connectivity and was transformed into the natural product atlanticone C (9 steps, 6 % overall yield). In addition, it was shown that other protoilludanes, such as Δ 6 ‐protoilludene and paesslerin A, can be prepared in a concise fashion via the photochemical key intermediate. The photochemical reaction cascade comprises an ortho photocycloaddition, a thermal disrotatory ring opening and a regioselective disrotatory [4π] photocyclization. Abstract : Magische Momente : Nach der Bestrahlung wurde das leicht zugängliche Indanon 1 (4 Stufen, 57 %) in einem einzigen Schritt in das komplexe tetracyclische Produkt 2 umgewandelt, das alle Kohlenstoffatome des Protoilludanskeletts enthält. Verbindung 2 diente der Synthese von Atlanticone C (3 ) und erwies sich als nützliches Zwischenprodukt für die Synthese anderer Protilludane.